Differential effects of motor cortical excitability and plasticity in young and old individuals: a Transcranial Magnetic Stimulation (TMS) study - Bashir, Shahid; Perez, Jennifer M.; Horvath, Jared C.; Pena-Gomez, Cleofe; Vernet, Marine; Capia, Anuhya; Alonso-Alonso, Miguel; Pascual-Leone, Alvaro (Frontiers in Aging Neuroscience, 2014)
Aging is associated with changes in the motor system that, over time, can lead to functional impairments and contribute negatively to the ability to recover after brain damage. Unfortunately, there are still many questions surrounding the physiological mechanisms underlying these impairments. We examined cortico-spinal excitability and plasticity in a young cohort (age range: 19-31) and an elderly cohort (age range: 47-73) of healthy right-handed individuals using navigated transcranial magnetic stimulation (nTMS). Subjects were evaluated with a combination of physiological (motor evoked potentials (MEPs), motor threshold (MT), intracortical inhibition (ICI), intracortical facilitation (ICF), and silent period (SP)) and behavioral (reaction time (RT), pinch force, 9 hole peg task (HPT)) measures at baseline and following one session of low-frequency (1 Hz) navigated repetitive TMS (rTMS) to the right (non-dominant) hemisphere. In the young cohort, the inhibitory effect of 1 Hz rTMS was significantly in the right hemisphere and a significant facilitatory effect was noted in the unstimulated hemisphere. Conversely, in the elderly cohort, we report only a trend toward a facilitatory effect in the unstimulated hemisphere, suggesting reduced cortical plasticity and interhemispheric commuinication. To this effect, we show that significant differences in hemispheric cortico-spinal excitability were present in the elderly cohort at baseline, with significantly reduced cortico-spinal excitability in the right hemisphere as compared to the left hemisphere. A correlation analysis revealed no significant relationship between cortical thickness of the selected region of interest and MEPs in either young or old subjects prior to and following rTMS. When combined with our preliminary results, further research into this topic could lead to the development of neurophysiological markers pertinent to the diagnosis, prognosis, and treatment of neurological